(untitled) (Research, Society and Development, 2022)
Objective: This study aimed to identify and define which factors interfere with adherence to type 2 Diabetes Mellitus (DM2) self-care activities. Methods: A hundred three (103) adults both sexes, diagnosed with Type 2 Diabetes Mellitus, have participated in this study. They were assessed through a socioeconomic questionnaire, Diabetes Self-Care Activities Questionnaire (DSCAQ) and International Physical Activity Questionnaire. (IPAQ). The study was carried out in the city of Três Corações-MG, from August 2018 to October 2019. Results: In the DSCA questionnaire, the activity with the highest adherence was related to medication intake (6,52 days ±1,52) and the lowest adherence was the activity related to the practice of specific physical exercises (1,29 days ±2,11). The IPAQ questionnaire determined that 66.0% of the participants reached the physical activity recommendations from the American Diabetes Association. By identifying the factors that interfere with adherence to self-care activities with DM2 and physical activity recommendation it was found through the cluster analysis Pearson’s chi-square that the education low level (p <0,001) and glycated hemoglobin low index (p = 0,032) were significant in the discrimination of groups when considering the variables of non-adherence to self-care activities. The education low level (p<0,001), in turn, was a significant factor in discrimination of groups, considering the variables of non-adherence to physical activity recommendations. Conclusion: It was possible to demonstrate that social and clinical factors may influence adherence to the patients diagnosed with DM2 treatment.